PERBANDINGAN MATCHING IMPEDANSI ANTENA DIPOLE SEDERHANA 152 MHz DENGAN ANTENA DIPOLE GAMMA MATCH 152 MHz - Candra, Henry; Ferdinansyah, Ferdinansyah (Jurnal Teknik Elektro, 2009)
Simple dipole antenna is an antenna which made from copper and precision size to be resonated in adjustable frequency. While gamma match dipole antenna is an antenna made with gamma match system which with adding capacitor in feed point .The design and realization of the two antennas above are compared to analyze the characteristics of both antennas to find out which has better radiation pattern, free space loss and gain antenna so it could be determined which antenna is suitable to use. The results show that both antennas have omnidirectional radiation pattern. The value of free space loss simple dipole antenna and gamma match dipole antenna is the same about 14.86 dB. The gain of simple dipole antenna is about 39.95 dB and the gain of gamma match antenna is 42.9 dB. Keywords: Antenna, Dipole, Matching Impedance, Gamma Match